Calcineurin governs baseline and homeostatic regulations of non–rapid eye movement sleep in mice - Xin Yin; Zihan Zhang; Rui Zhou; Peng Zuo; Di Sang; Shuang Zhou; Bihan Shi; Lin Chen; Chongyang Wu; Ying Guo; Fengchao Wang; Eric Erquan Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
Sleep need accumulates during waking and dissipates during sleep to maintain sleep homeostasis (process S). Besides the regulation of daily (baseline) sleep amount, homeostatic sleep regulation commonly refers to the universal phenomenon that sleep deprivation (SD) causes an increase of sleep need, hence, the amount and intensity of subsequent recovery sleep. The central regulators and signaling pathways that govern the baseline and homeostatic sleep regulations in mammals remain unclear. Here, we report that enhanced activity of calcineurin Aα (CNAα)—a catalytic subunit of calcineurin—in the mouse brain neurons sharply increases the amount (to ~17-h/d) and delta power—a measure of intensity—of non–rapid eye movement sleep (NREMS). Knockout of the regulatory ( CnB1 ) or catalytic ( CnAα and CnAβ ) subunits of calcineurin diminishes the amount (to ~4-h/d) and delta power of baseline NREMS, but also nearly abrogates the homeostatic recovery NREMS following SD. Accordingly, mathematical modeling of process S reveals an inability to accumulate sleep need during spontaneous or forced wakefulness in calcineurin deficient mice. Moreover, calcineurin promotes baseline NREMS by antagonizing wake-promoting protein kinase A and, in part, by activating sleep-promoting kinase SIK3. Together, these results indicate that calcineurin is an important regulator of sleep need and governs both baseline and homeostatic regulations of NREMS in mice.